2020
DOI: 10.3390/brainsci10030179
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Resistance Affects Medium-Term Recurrent Vascular Events after Cerebrovascular Incidents: A Three-Year Follow-up Study

Abstract: Background: The aim of this prospective, a three-year follow-up study, was to establish the role of high on-treatment platelet reactivity (HTPR) in predicting the recurrence of vascular events in patients after cerebrovascular incidents, particularly in the aspect of stroke etiology. Methods:The study included 101 subjects with non-embolic cerebral ischemia (69 patients with ischemic stroke and 32 patients with transient ischemic attack) treated with 150 mg of acetylsalicylic acid (aspirin) a day. The platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The most common event is another recurrent stroke or transient ischemic attack, but stroke subjects are also at a higher risk of myocardial infarction (MI), sudden cardiac death, acute limb ischemia, or systemic embolism. Previous studies regarding aspirin resistance have demonstrated a significant, independent association between high on-treatment platelet reactivity and a higher risk of recurrent vascular events in stroke subjects [51]. The data on clopidogrel therapy are consistent.…”
Section: Recurrent Vascular Eventssupporting
confidence: 59%
“…The most common event is another recurrent stroke or transient ischemic attack, but stroke subjects are also at a higher risk of myocardial infarction (MI), sudden cardiac death, acute limb ischemia, or systemic embolism. Previous studies regarding aspirin resistance have demonstrated a significant, independent association between high on-treatment platelet reactivity and a higher risk of recurrent vascular events in stroke subjects [51]. The data on clopidogrel therapy are consistent.…”
Section: Recurrent Vascular Eventssupporting
confidence: 59%
“…The mechanisms leading to a low biological response to antiplatelet agents and the incidence of aspirin and clopidogrel resistance are similar, both in ischemic stroke and coronary heart disease. A significant negative impact of the phenomenon on many clinical aspects in both diseases was reported, including a severe clinical course, poor early and late prognosis, an unfavorable clinical outcome, and a higher risk of recurrent vascular events [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our next study we underlined that stroke subjects with large vessel disease and high on‐aspirin platelet reactivity have significantly larger volume of acute ischaemic infarct and severity of chronic ischaemic lesions compared with normal on‐aspirin platelet reactivity strokes 5 . We also emphasised that stroke subjects with aspirin nonresponsiveness are more likely to develop medium‐term (3 to 9 months) recurrent vascular events, in particular the next ischaemic stroke 6 . The above findings undoubtedly suggest a negative impact of aspirin ineffectiveness on poor clinical outcome, in particular among smoking males with large vessel disease as a cause of stroke.…”
mentioning
confidence: 84%
“…5 We also emphasised that stroke subjects with aspirin nonresponsiveness are more likely to develop medium-term (3 to 9 months) recurrent vascular events, in particular the next ischaemic stroke. 6 The above findings undoubtedly suggest a negative impact of aspirin ineffectiveness on poor clinical outcome, in particular among smoking males with large vessel disease as a cause of stroke. Moreover, our findings regarding aspirin are consistent with the results obtained by other authors.…”
mentioning
confidence: 99%